PERANCANGAN BUKU CERITA ANAK BERGAMBAR SEBAGAI MEDIA PENGENALAN SENI BELADIRI SILEK HARIMAU - James Trisno; Yana Erlyana (ULTIMART Jurnal Komunikasi Visual, 2023)
Indonesia has a martial art, namely the martial art of Pencak Silat. Pencak Silat has various variations due to the diversity of cultures in Indonesia. Unfortunately, Pencak Silat is currently less in demand due to various reasons, but one of them is competition with foreign martial arts. One of the martial arts of Pencak Silat whose existence is threatened is the martial art of Silek Harimau, this is made worse by the absence of written documentation regarding Silek Harimau. Therefore, this design aims to create media in the form of illustrated children's story books that introduce Silek Harimau to children. This design will use descriptive qualitative research methods, and data collection methods in the form of interviews, observations, literature studies, and questionnaire surveys. The design will use the Design Thinking method which consists of various stages, namely: Emphasize, Define, Ideate, Prototype, and Test. These design stages will later produce a media in the form of a illustrated children's story book entitled "Menjadi Kesatria Harimau" Keywords: martial arts; children; picture book; stories